2003
DOI: 10.1590/s0102-05362003000200013
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da concentração de nitrogênio na solução nutritiva e do número de frutos por planta sobre a produção do meloeiro

Abstract: ABSTRACT) and fruit number per plant (2; 3; 4 and free setting), were investigated on net melon production (Cucumis melo var. reticulatus, Bonus n o 2 hybrid). The experiment was carried out in Jaboticabal, São Paulo State, Brazil, in NFT hydroponic system, from June to November, 2001. The experimental design was of randomized split plots, replicated six times. At 80 days after seedling transplant 2; 3; 4 and 5.1 fruits per plant were found. However, at harvest there were 2; 2.9; 3.0 and 3.4 fruits per plant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 5 publications
1
8
0
14
Order By: Relevance
“…Além disso, a produção na época de entressafra de outros países também vem facilitando a ampliação do mercado nacional no exterior (Negreiros et al, 2003). O plantio de melões rendilhados concentra-se nas regiões Sul e Sudeste do Brasil, caracterizando-se por cultivos efetuados em casas de vegetação, sendo que estes vêm aumentando nos últimos anos (Purquerio, 2002) …”
Section: Desempenho De Cultivares De Melão Rendilhado Em Função Do Siunclassified
“…Além disso, a produção na época de entressafra de outros países também vem facilitando a ampliação do mercado nacional no exterior (Negreiros et al, 2003). O plantio de melões rendilhados concentra-se nas regiões Sul e Sudeste do Brasil, caracterizando-se por cultivos efetuados em casas de vegetação, sendo que estes vêm aumentando nos últimos anos (Purquerio, 2002) …”
Section: Desempenho De Cultivares De Melão Rendilhado Em Função Do Siunclassified
“…Essa qualidade está relacionada ao manejo que a cultura recebe até o momento da colheita (CHITARRA & CHITARRA, 1990 Com a consolidação do cultivo de hortaliças em casa de vegetação, o cultivo do melão rendilhado recebeu maior atenção dos produtores, especialmente nos estados de São Paulo e Paraná, como opção rentável no cultivo protegido (PURQUERIO, 2002). Esse sistema se expandiu a partir de 1990, com a possibilidade de exportação e a perspectiva de novos nichos de mercado, com a expansão das grandes redes de supermercados no país.…”
Section: Introductionunclassified
“…Considering that the 'Gália' melon packing box for exportation generally has a capacity for 5 kg, holding 4 to 9 fruits (EMBRAPA, 2010) and the minimum fruit weight for exportation of 555 g (Filgueiras et al, 2000), from the concentration of 12.5% up to 88%, the produced fruits had the minimum size for exportation. Purquerio et al (2003) grew 'Bônus nº 2' melon in NFT hydroponic system and observed that the increase of N concentration in the nutrient solution reduced the mean weight of the fruits. The authors obtained mean weights of 675, 655 and 624 g fruit -1 , at N concentrations of 237, 248 and 300 mg L -1 , respectively.…”
Section: Fruit Productionmentioning
confidence: 99%
“…Purquerio & Cecílio Filho (2005) observed reduction of 6.9% in melon pulp thickness with the increment of N dose in the nutrient solution from 80 to 300 mg L -1 . According to Purquerio et al (2003), the reductions of TD, LD and PT are responsible for the reduction in fruit weight, and consequently yield, which also decreased with the increment in the N concentration in the solution.…”
Section: Fruit Qualitymentioning
confidence: 99%